Knowing nursing through its evolutionary descriptions the definitions of nursing - Abalos, Evalyn E. (2010)
Nursing has emerged from being an occupation to an emerging profession. It is now viewed as an academic discipline and a human science. Its evolutionary 'journey' has to be revisited so that present-day nursing can be better understood and appreciated. Its evolution to what it is at present can be traced in several ways. These may be by time periods or eras, nursing roles, process of professionalization, and knowledge development, among others. There is a myriad of factors that have impacted and will continue to impact nursing in different countries worldwide. To date, the descriptions and definitions of nursing are still difficult to grasp owing to the intertwine of influences that have impinged on it. What are the milestones of its journey? What is the future of Nursing? Where is nursing going? Only time can tell as it continues its process of unfolding.
Keywords: Nursing